Radio-Tartaglia Syndrome: A Rare Cause of Delay in Neurodevelopment - A Case Report - Maria Arteaga Pichardo; Felipe Bernate; Juan Trujillo Angel; Maria Santana Alba; Maria Lubo; Natalia Avellaneda Perdigon; Lev Bladimir Ramirez; Daniel Jimenez; Sofia Atuesta Escobar; Isabel Fernandez Gonzalez; Luis Celis Regalado (Mashhad University of Medical Sciences, 2024)
Background: Radio-Tartaglia syndrome or RATARS is an unfamiliar disease caused by a heterozygous mutation of the SPEN gen in the 1p36 chromosome. Clinically, it is represented by global developmental delay and intellectual disability; however, it can also be associated with other relevant comorbidities that embark on the cardiovascular, gastrointestinal, musculoskeletal, integumentary as well as endocrinological systems. Case Report: A 3-year-old pediatric male patient from Venezuela is referred to genetic counseling due to neurodevelopmental delay, microcephaly and dysmorphisms. The initial diagnostic impression consisted of Williams syndrome. Further studies revealed mild supravalvular stenosis, but no important changes in brain imaging or laboratory analysis. The patient's diagnosis was later replaced with RATARS after a complete exome sequencing revealed heterozygous SPEN pathogenic genes. Conclusion: The diagnostic process of RATARS must become a pillar of further investigation given its uncertainty when clinically diagnosed hence the necessity of a clear confirmation through exome sequencing. This case report highlights the importance of genetic testing in patients with neurodevelopmental delay due to a possible but uncommon correlation with rare diseases such as RATARS.